Film Festivals From European Geopolitics to Global Cinephilia - de Valck, Marijke (Film Culture in Transition, 2007)
Film festivals are hugely popular events that attract lovers of cinema worldwide. Focusing on the world's most famous festivals - Cannes, Berlin, Venice and Rotterdam - Film Festivals tells the story of a phenomenon that began in the midst of geopolitical disputes in war-torn Europe. De Valck shows how festivals turned the odds into advantages and developed into a successful global network. Taking into account the oft multilateral influences of major actors, such as Hollywood, the avant-garde and political/economic agenda's, the book offers a comprehensive understanding of film festivals. A must-read for everyone interested in quality film cultures that revolve around cultural value, aesthetic innovation and socio-political relevance.